1990
DOI: 10.1111/j.1523-536x.1990.tb00021.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Evaluation of Early Postpartum Hospital Discharge

Abstract: At approximately 37 weeks' gestation, 131 women were randomly assigned to one of three postpartum hospital discharge times: 12 to 24 hours, 25 to 48 hours, and 4 days. Depending on group assignment, the women received from one to five home visits by a maternity nurse clinician during the first 10 days postpartum. The results indicated the maternal and infant morbidity were low regardless of discharge time, although sample sizes were too small to detect significant differences in the outcomes. More early discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
101
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 11 publications
3
101
0
5
Order By: Relevance
“…3 The evidence for and against early discharge remains inconclusive. 9,[12][13][14] Most studies have involved small groups of randomized volunteers 15,16 or have used large data-base samples without control for possible effects of selection among newborns who are discharged early. Several studies have suggested that short stays are associated with an increased risk of death or readmission of the infant, 17,18 whereas others have found no effect.…”
Section: Resultsmentioning
confidence: 99%
“…3 The evidence for and against early discharge remains inconclusive. 9,[12][13][14] Most studies have involved small groups of randomized volunteers 15,16 or have used large data-base samples without control for possible effects of selection among newborns who are discharged early. Several studies have suggested that short stays are associated with an increased risk of death or readmission of the infant, 17,18 whereas others have found no effect.…”
Section: Resultsmentioning
confidence: 99%
“…Early discharge of healthy new borns after delivery has become a common practice because of social reasons, medical and economic constraints. 3 However decreased length of hospital stay is found to increase the risk of readmission to the hospital. 4,5 This necessitates a study to identify the incidence of neonatal hyperbilirubinemia in the present day community.…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, this paper attempts to identify risk factors for short-stay, medium-stay and long-stay subgroups of patients, and analyzes LOS as an indicator of the pressure on inpatient treatment, with a view to enhancing standardization of the curative healthcare delivery system in India. From both the physical and mental health perspectives of patients, the shorter the recovery time (in terms of shorter LOS), the more effective is the curative treatment [4][5][6].…”
Section: Introductionmentioning
confidence: 99%